Effects of Combined Exercise Program on Body Composition, Lipid and Cortisol Levels in Blood among Middle School Students with Intellectual Disability - Park, Kun-Woo; Kim, Seung-Yong (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The purpose of this study was to identify physiological responses through combined exercddise for intellectually disabled people who view obesity as one of their physical characteristics. To achieve the purpose of this study, an eight-week compound exercise was conducted on 28 intellectually disabled middle school students residing in K city and the average and standard deviation for groups (normal BMI groups, obese BMI groups) were calculated. In addition, data processing was performed using two way repeated measured ANOVA using SPSS 18.0, and post-verification was performed if there were significant differences. The results are as follows: First, there was no change in weight for middle school students with intellectual disabilities through eight weeks of combined exercise. However, the lean body mass increased in the standard population, body fat mass and BMI decreased in the standard population, and the bone density factor increased in both the standard population and the obese population. Second, neutral fat decreased in the standard group, and the low-density cholesterol factor decreased in the obesity group. Third, cortisol factors have been shown to decrease in standard groups. In conclusion, the eight-week compound exercise has been shown to have an effect of improvement in the physical composition and blood lipid variables of middle school students with intellectual disabilities.